Analysis of Factors Influencing Impulsive Buying in Luza Idea Consumers - Islamidina, Shafa Syahida; Barkah, Cecep Safa'atul; Chan, Arianis; Tresna, Pratami Wulan (Journal of Business & Applied Management, 2023)
This study purposed to determine the factors that influence impulsive buying in Luza Idea consumers and provide recommendations for appropriate strategies to increase sales by considering the factors that most influence the impulsive buying of its consumers. The variables in this study are product characteristics (X1), marketing characteristics (X2), consumer characteristics (X3), and impulsive buying (Y). This type of research is quantitative research with descriptive methods. The conclusions in this study resulted in consumer characteristics as the variable that most influenced impulsive buying in Luza Idea consumers. Based on the results of the VRIO analysis, it shows that Luza Idea needs to increase the superiority of its product characteristics in terms of serviceability and aesthetics aspects. Then, from the characteristics of marketing, Luza Idea needs to increase its advantages in the aspect of its product offering.